Multicomponent Exercise Program in Older Adults with Lung Cancer During Adjuvant/Palliative Treatment: A Secondary Analysis of an Intervention Study - Garcia-Hermoso, A (Serdi-Editions, 2021)
Background: Lung cancer is the second most prevalent common cancer in the world and predominantly affects older adults. This study aimed to examine the impact of an exercise programme in the use of health resources in older adults and to assess their changes in frailty status. Design: This is a secondary analysis of a quasi-experimental study with a non-randomized control group. Setting: Oncogeriatrics Unit of the Complejo Hospitalario de Navarra, Spain. Participants: Newly diagnosed patients with NSCLC stage I-IV. Intervention: Multicomponent exercise programme that combined resistance, endurance, balance and flexibility exercises. Each session lasted 45–50 minutes, and the exercise protocol was performed twice a week over 10 weeks. Measurements: Mortality, readmissions and Visits to the Emergency Department. Change in frailty status according to Fried, VES-13 and G-8 scales. Results: 26 patients completed the 10-weeks intervention (IG). Mean age in the control group (CG) was 74.5 (3.6 SD) vs 79 (3 SD) in the IG, and 78,9% were male in the IG vs 71,4% in the CG. No major adverse events or health-related issues attributable to the testing or training sessions were noted. Significant between-group differences were obtained on visits to the emergency department during the year post-intervention (4 vs 1; p:0.034). No differences were found in mortality rate and readmissions, where an increasing trend was observed in the CG compared with the IG in the latter (2 vs 0; p 0.092). Fried scale was the unique indicator that seemed to be able to detect changes in frailty status after the intervention. Conclusions: A multicomponent exercise training programme seems to reduce the number of visits to the emergency department at one-year post-intervention in older adults with NSCLC during adjuvant therapy or palliative treatment, and is able to modify the frailty status when measured with the Fried scale. © 2021, Serdi and Springer Nature Switzerland AG.